(untitled) (Bioresearch Communications, 2023)
Thalassemia is one of the most common genetic disorders in Bangladesh. We have performed an investigation among 360 patients with Hb E/β-thalassemia to understand the heterogeneity in thalassemia severity among Bangladeshi patients. The analysis revealed that one of the common mutations CD26 (G>A) is found with two rare mutations HBB: c.-79A>G (-29A>G) and HBB: c.45_46insG (CD14/15 (+G)) in two patients individually which are not prevalent in geographically adjacent populations. Among these two rare mutations, -29A>G is located at the ‘TATA’ box region of the promoter sequence regulating transcription initiation and CD14/15 (+G) leads to a premature stop codon. We performed transcription factor binding site prediction analysis and found that ‘AP-1’, ‘c-Jun’, and ‘kr’ transcription factors bind at the ‘TATA’ box region. From this analysis, we can predict that -29A>G mutation can alter the level of HBB transcription whereas the CD14/15 (+G) mutation causes a truncated (and possibly non-functional) HBB protein. Aligned with such assumption, it was observed from patients’ medical history that, the patient who had CD14/15 (+G) and CD26 (G>A) mutations was severely blood transfusion-dependent whereas the patient carrying -29A>G and CD26 (G>A) mutations was moderately transfusion dependent. The comprehensive analysis of the mutations offers crucial insights and approaches for enhanced management of thalassemia among the Bangladeshi population. Bioresearch Commu. 10(1): 1442-1448, 2024 (January)